(untitled) (Biological Sciences - PJSIR, 1999)
The recommended method of "broadcasting and incorporation" of solid P fertilizer before sowing was compared and evaluated against "top dressing" ofP after plantemergance and as "solution application" along with irrigation water (termed fertigation) by growing wheat in pot and field experiments. The lower Prate applied by fertigation at first irrigation resulted in equivalent wheat yield and 25-30% higher P fertilizer efficiency compared to higher rate applied broadcast and incorporated at sowing, indicating the possibility of substantial saving in P fertilizer input.